2022
DOI: 10.3390/su141710510
|View full text |Cite
|
Sign up to set email alerts
|

The Educational Use of WhatsApp

Abstract: The mobile phone has become the preferred means of communication, especially among young people, and there are many teachers who are committed to introducing it as a resource in their classrooms. Therefore, the objective of this work was to describe the educational uses of WhatsApp. The methodology was a systematic review of published work on the subject, based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) and similar phases in the process. The sample was made up of 192 pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 60 publications
0
7
0
1
Order By: Relevance
“…With the increase in the ownership of smartphones by university students and the ease of use and affordability of WhatsApp in the higher education learning environment, many studies recognise that WhatsApp is of "potential for ubiquitous learning, and the students have a good attitude to this app as a teaching and learning platform" [12] (p. 8). Results from 192 papers obtained from the Google Scholar database show the educational use of WhatsApp resulted in: (1) enhanced students' academic performance, (2) an improvement in efficiency, time planning and organisation, active learning, decision making and motivation, (3) high levels of satisfaction among students and teachers who used the application and (4) its suitability as an educational and support resource in teaching and learning processes at all educational stages [12].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…With the increase in the ownership of smartphones by university students and the ease of use and affordability of WhatsApp in the higher education learning environment, many studies recognise that WhatsApp is of "potential for ubiquitous learning, and the students have a good attitude to this app as a teaching and learning platform" [12] (p. 8). Results from 192 papers obtained from the Google Scholar database show the educational use of WhatsApp resulted in: (1) enhanced students' academic performance, (2) an improvement in efficiency, time planning and organisation, active learning, decision making and motivation, (3) high levels of satisfaction among students and teachers who used the application and (4) its suitability as an educational and support resource in teaching and learning processes at all educational stages [12].…”
Section: Literature Reviewmentioning
confidence: 99%
“…A recent systematic review on the educational use of WhatsApp shows the advantages and disadvantages or difficulties in the educational use of WhatsApp [12]. The review concluded that although WhatsApp was not designed for the educational environment, its affordances and advantages can be shown to be "an adequate educational and support resource in teaching and learning at all educational stages.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is consistent with similar findings in the literature that confirm the abundant use of social media platforms, such as WhatsApp, for learning. Suárez-Lantarón et al (2022), for example, acknowledged that WhatsApp is the leading instant messaging application in the world at the moment. Similarly, Baishya and Maheshwari (2019) noted that students mainly possess mobile smartphones and can interact in online learning by collaboratively working on some assigned work.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…El internet se volvió indispensable y los dispositivos móviles, con todas sus aplicaciones, posibilitaron procesos de agrupación y de vinculación interpersonal. Una de las aplicaciones tecnológicas de comunicación más utilizada fue y sigue siendo WhatsApp, la cual surgió en 2009 (1) , descrita como una aplicación de mensajería instantánea por medio de la cual se pueden enviar y recibir imágenes, vídeos, audios, documentos, entre otras funciones.…”
Section: Sobre La Información La Seguridad Y La Emociónunclassified